A new species of Stigmaeus (Acari: Trombidiformes: Stigmaeidae) from Brazil - Saeid Paktinat-Saeij; Mohammad Bagheri; Jorge L. Muñoz Marticorena; Gilberto J. de Moraes (Persian Journal of Acarology)
A new species of the genus Stigmaeus, S. brasiliensis sp. nov. is described based on females, males and deutonymphs, collected from the São Paulo state, Brazil.